Interrelationship of superficial siderosis and microbleeds in cerebral amyloid angiopathy - Shoamanesh, Ashkan (Neurology, 2014)
OBJECTIVE: We sought to explore the mechanisms leading to cerebral amyloid angiopathy (CAA)-related cortical superficial siderosis (cSS) by examining its neuroimaging and genetic association with cerebral microbleeds (CMBs). METHODS: MRI scans of 84 subjects with probable or definite CAA participating in a longitudinal research study were graded for cSS presence and severity (focal, restricted to ≤3 sulci vs disseminated, ≥4 sulci), and CMB count. APOE ε variants were directly genotyped. We performed cross-sectional analysis comparing CMB counts and APOE ε2 and ε4 allele frequency between subjects with no, focal, or disseminated cSS. RESULTS: cSS was present in 48% (n = 40) of the population. APOE ε2 was overrepresented among participants with focal (odds ratio [OR] 7.0, 95% confidence interval [CI] 1.7–29.3, p = 0.008) and disseminated (OR 11.5, 95% CI 2.8–46.2, p = 0.001) cSS relative to individuals without cSS. CMB counts decreased with increasing severity of cSS (median: 41, 38, and 15 for no cSS, focal cSS, and disseminated cSS, respectively, p = 0.09). The highest CMB count tertile was associated with APOE ε4 (OR 3.0, 95% CI 1.4–6.6, p = 0.006) relative to the lowest tertile. CONCLUSIONS: Among individuals with advanced CAA, cSS tends to occur in individuals with relatively lower CMB counts and with a distinct pattern of APOE genotypes. These results suggest that CAA-related cSS and CMBs may arise from distinct vasculopathic mechanisms.